Pengaruh Konsep Diri, Kemandirian Belajar, Kesiapan Belajar, Perhatian Orangtua Dan Fasilitas Belajar Terhadap Hasil Belajar Siswa Kelas Xi IPS Pada Mata Pelajaran Ekonomi di SMA Negeri 2 Batang Anai - Mesi Utami; Rika Verawati; Meri Rahmania (STKIP PGRI Sumatera Barat, 2022)
This study aims to analyze the sampling technique using the Proportional Random Sampling method. The sample in this study was 98 students. The results of self-concept research have a significant effect on learning outcomes. the respective coefficients are 0.188. With the value of tcount tcount 3.193 > ttable 1.66159 This means that if self-concept increases by one unit, then learning outcomes increase by 0.188 in each unit. Independent learning is significant to learning outcomes. The respective coefficients are 0.315. learning readiness has a significant effect on learning outcomes. the respective coefficients are 0.320. Parental attention has a significant effect on learning outcomes. the respective coefficients are 0.437. Learning facilities have a significant effect on learning outcomes. their respective coefficients are 0.208. self-concept, learning independence, learning readiness, parental attention and learning facilities together have a significant effect on learning outcomes. Where obtained the value of Fcount 45.625 > Ftable 2.31 with a significant level of 0.000 < = 0.05. This means that Ha is accepted and H0 is rejected.Keywords: Self-concept, learning independence, learning readiness, parental attention and learning facilities.